1999
DOI: 10.1016/s0014-5793(99)00969-2
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin mediated apoptosis in AK‐5 tumor cells involves the production of reactive oxygen intermediates

Abstract: Curcumin, the active ingredient of the rhizome of Curcuma longa has anti-inflammatory, antioxidant and antiproliferative activities. Although its precise mode of action remains elusive, studies have shown that chemopreventive action of curcumin might be due to its ability to induce apoptosis in cancer cells. Curcumin was shown to be responsible for the inhibition of AK-5 tumor (a rat histiocytoma) growth by inducing apoptosis in AK-5 tumor cells via caspase activation. This study was designed to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
112
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(131 citation statements)
references
References 31 publications
16
112
0
3
Order By: Relevance
“…Our results are in agreement with previous findings suggesting that ROS are needed for the apoptotic effects of curcumin [18,[58][59][60][61][62]. Indeed, we found that depletion of endogenous GSH augmented curcumin-induced cell death in tumor cells.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in agreement with previous findings suggesting that ROS are needed for the apoptotic effects of curcumin [18,[58][59][60][61][62]. Indeed, we found that depletion of endogenous GSH augmented curcumin-induced cell death in tumor cells.…”
Section: Discussionsupporting
confidence: 94%
“…These results are in agreement with previous reports that showed that curcumin suppresses the proliferation of a wide variety of tumor cells (Mehta et al, 1997;Anto et al, 2002;Kuo et al, 1996;Jiang et al, 1996;Ranjan et al, 1999;Piwocka et al, 1999;Han et al, 1999;Simon et al, 1998;Ramachandran and You, 1999;Bhaumik et al, 1999), including both B cell and T cell leukemia, colon carcinoma, breast carcinoma, prostate cancer cells and other tumor cell types. How curcumin suppresses the proliferation of tumor cells is not well understood.…”
Section: Figuresupporting
confidence: 93%
“…We and others have previously shown that curcumin (diferuloylmethane), a chemopreventive agent, is a potent down-regulator of NF-kB activation, most likely through the suppression of IkBa kinase (IKK) needed for NF-kB activation and it inhibits NFkB-mediated gene expression (Singh and Aggarwal, 1995;Kumar et al, 1998;Plummer et al, 1999;Jobin et al, 1999). Curcumin is also known to suppress the proliferation of a wide variety of tumor cells, including breast and prostate cancer cells (Mehta et al, 1997;Anto et al, 2002;Kuo et al, 1996;Jiang et al, 1996;Ranjan et al, 1999;Piwocka et al, 1999;Han et al, 1999;Simon et al, 1998;Ramachandran and You, 1999;Bhaumik et al, 1999), through a mechanism which is incompletely understood. We hypothesized that curcumin must mediate its antiproliferative effects through down-regulation of cyclin D1.…”
Section: Introductionmentioning
confidence: 99%
“…2013), and prostate cancer cells (Chen, 2015). A high correlation was found between curcumin-mediated apoptosis and intracellular ROS (Bhaumik et al, 1999). A recent study reported that curcumin inhibits proliferation of colon cancer cell lines by arresting cells in G2-M phase (Hanif et al, 1997), down-regulates the expression of bcl-2 in tumor cells and induces apoptosis in NIH3T3 and leukemic cell line HL-60 (Jiang et al, 1996;Kuo et al, 1996).…”
Section: Introductionmentioning
confidence: 92%